Mathew Brady : his life and photographs - Sullivan, George, 1927- (New York : Cobblehill Books, 1994)
The story of the life and vision of Mathew Brady, the renowned photographer of the Civil War.
Includes bibliographical references (p. [129]-131) and index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
6.9
5-8.
Keywords: Brady, Mathew B., -- 1823 (ca.)-1896 -- Juvenile literature; Brady, Mathew B., -- 1823 (ca.)-1896.; Brady, Mathew B., -- 1823 (ca.)-1896.; Photographers -- United States -- Biography -- Juvenile literature; Portrait photography -- United States -- History -- Juvenile literature; Photographers; Photographers; Portrait photography -- History; United States -- History -- Civil War, 1861-1865 -- Photography -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Photography; United States -- History -- 1861-1865, Civil War